Experimental investigation of methods for remediation of approach slab settlements in integral abutment bridges - Yenne, Justin (Kansas State University, 2024)
Traditional bridges incorporate costly deck expansion joints that accommodate temperature induced expansion and contraction. Construction and life time maintenance of these joints impose a significant financial burden on their owners that lead to a paradigm shift resulting in development of integral bridges. Abutments of integral abutment bridges (IABs) are seamlessly monolithically connected to girders. In fully integral bridges abutments are also monolithically connected to piles. These bridges offer numerous advantages, such as enhanced resilience, increased redundancy, decreased construction and maintenance costs, and improved quality of vehicular ride. However, the absence of expansion joints in IABs introduces difficulties associated with thermal load transfer. IABs’ decks and girders undergo ambient temperature induced cyclic seasonal expansions and contractions that affect their short- and long-term behaviors. The cyclic abutment movements, towards and away from the retained backfill soil lead to a long-term buildup of the lateral earth pressure and settlement of the backfill resulting in the formation of a subsidence zone and distress of the approach slab, also known as a “bump” at the end of the bridge. The onset of a void formation often starts early after the construction of the bridge had been completed. This thesis experimentally investigated methods for alleviation of bridge approach settlement in IABs. This was accomplished by conducting experiments on a down- scaled model of an existing integral bridge. The model abutment supported by piles and surrounded by the selected backfill soil was subjected to 100 cycles of backward-forward motion simulating the action of seasonal cyclic changes of ambient temperature. Explored alleviation methods include use of geogrid, geotextile, different configurations of expanded polystyrene (EPS) geofoam inclusions, and different combinations of EPS geofoam and geogrid, and EPS geofoam and geotextile reinforcements. Additionally, the backfill soil failure and collapse mechanisms that contribute to development of bridge approach settlement were captured by use of digital camera and digital imaging correlation (DIC) software, a technique originating from fluid mechanics. It was found that use of geotextile and EPS geofoam, and geogrid and EPS foam were the best performing alleviation methods overall. The insights gained from this study are crucial for alleviating bridge approach settlements in IABs, and further decreasing the maintenance costs while ensuring sustained efficiency and durability of integral bridges and transportation lifelines.
Keywords: Integral bridge; Backfill collapse; Bridge approach settlement; Drained cyclic loading; Backfill failure; Geosynthetics